Coronary CT Angiography Findings with 64-Detector CT (Annals of Medical Research, 2021)
Aim: This study aims to determine the coronary artery variations, anomalies, and pathologies that could be detected in coronarycomputed tomography angiography (CCTA).Materials and Methods: Between March 2007 and December 2008, 1180 patients were referred to our clinic with CCTA requests.Coronary artery anatomy, the presence of variations and anomalies, coronary artery disease, proximal and distal anastomosis levels,stenosis and/or occlusion of by-pass grafts, stent patency, or stenosis were examined and recorded for all cases.Results: Total of 1118 cases included in the study. The left main coronary artery (LM) was not observed in 9 (0.80%) patients. In onecase (0.08%), the circumflex artery (LCx) artery was originated from the right sinus of Valsalva (RSV) with a retro-aortic course andthen reached its typical trace. The LM originated from the RSV in 2 patients (0.17%). The right coronary artery (RCA) originated fromthe left sinus of Valsalva (LSV) in 4 cases (0.35%). Coronary artery disease (CAD) in any stage was found in 100 patients with zeroscores, and 27 (4.48%) had stenotic CAD according to CCTA. There was a moderate correlation between age and CAD stage, and ageand calcium (Ca) score.Conclusion: In conclusion, 64-MDCT coronary angiography is a suitable method for the noninvasive evaluation of coronary arteries.Coronary artery anomalies are observed with a non-rare frequency. There is a moderate correlation between age and CAD sta